THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION AT THE SECOND YEAR STUDENTS OF SMPN 3 GUNUNGSARI - Sudirman Sudirman (Universitas Pendidikan Mandalika, 2017)
The research entitled The Correlation Between Vocabulary Mastery and Reading Comprehension aims at finding out there is whether any correlation between vocabulary mastery and reading comprehension at the second year students of SMPN 3 Gunungsari. This research was designed by using descriptive quantitative method. The research took 30 students as sample of this study. To analyses the data this research used statistic computation by product moment correlation, to get the final score. The data found that the mean score of reading comprehension was 54.4 and vocabulary was 53,6. After computing by the statistical analysis of Product Moment, the value shows 1.631 while the t-table was 1.671 and 2.390. This result of this investigation indicated that there is no significant between vocabulary and reading comprehension. The value of t-test was 1.631 is lower than 1.671 and 2.390 in 0.05 and 0.01 significant level. While the degree of freedom (df) = 60. It can be concluded that there is no correlation between vocabulary mastery and reading comprehension.